(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The presented article discusses discretionary criminal prosecution as innovation in modern Georgian criminal procedural legislation. Legal aspects of criminal prosecution, its procedural regulation and practical implementation issues are discussed in the present work, which mainly deals with the prosecution, as the guiding principles of the prosecutor’s discretionary authority and prosecution functions in the investigation stage, Georgian model of general discretionary prosecution.